Gold-Related Deposits in the Southern Mountains of East Java, Indonesia - , L.D. Setijadji ([Yogyakarta] : Departemnts of Geological Engineering Faculty of E, 2009)
Many occurrences of mineral deposits are reported from the Southern Mountains of East Java, although none is already mined at industrial scale. Styles of mineralization vary from low-sulfidation epithermal Au-Ag, sediment-hosted, Au-base metals veins, high-sulfidation epithermal, skarn (Mn, Fe, and Cu-Zn-Pb), and porphyry Cu-Au. Several mineral districts contain cluster of different styles of mineralization. Few deposits in the Tirtomoyo and Pacitan districts have smallscale historical productions during the Dutch (pre- WW II) and Japanese (during WW II) colonialism periods. However, the more significant scale of mineralization features have now been identified from the Trenggalek (epithermal Au-Ag) and the Tumpangpitu district (porphyry Cu-Au). At the majority of the known deposits, spatial association of mineralization with Miocene intrusive rocks is found.